ANALISIS SISTEM PENGENALAN DAN KEAMANAN KRIPTOGRAFI HILL CIPHER PADA PLAT NOMOR KENDARAAN MENGGUNAKAN METODE TEMPLATE MATCHING - Ike Fibriani; Gebby Gumelar (Politeknik Aceh, 2016)
Technology progress is closely related to human efficiency in doing their jobs, one of them is the parking system.The high frequency parking vehicle out of a parking space would allow a computer to replace the role of human. The researcher will make a system that can recognize license plate automatically and have security system toward the license plate itself. License plate recognizing system in this research uses template matching method. Data collection method was conducted in the afternoon and night to know the effect of light intensity level toward system performance. In the afternoon, there were 9 of 10 correctly identified test images (90% accuracy). However, at night there were 8 of 10 correctly identified test images (80% accuracy). As a result, the total of system accuracy in the identification process was 85%. In the angle test of 0⁰ and -15⁰were obtained an accuracy 16.7% and 6.7%, while in the other angles can't be identified correctly. In the distance test of 1m was obtained an accuracy 12.7%, whereas in the other distance testscannotbe identified correctly. In data security process, the identified test images (in this case as plaintext) will be encrypted using cryptography hill cipher algorithm. From 20 plaintext data, there were 20 data that encrypted correctly, in other words cryptography hill cipher algorithm accuracy in the system was 100%.